Count your blessings : gratitude and subjective well-being in adolescent boys : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Irwin, Jane (Massey University, 2017)
The enhancement of well-being in schools using evidence-based interventions from the field of positive psychology is a growing field of interest. These interventions are based on the theory that sustainable changes in well-being can be achieved through regular engagement in simple and intentional activities. This study examines the effectiveness of a school-based gratitude diary intervention to promote subjective well-being in adolescent boys (age range 16 to 18 years). The gratitude intervention took place in a Catholic secondary school for boys for two weeks and involved two groups. One group of participants wrote in a diary about things that they were grateful for in the recent past, and a control group wrote in a diary about neutral events in the recent past. Participants who undertook the gratitude intervention did not demonstrate enhanced subjective well-being or gratitude relative to their pre-intervention measures or to those of the control group. Both the medians and means of the well-being measures of the boys in the gratitude condition were found to be lower post-intervention than preintervention, but the mean reduction in well-being was not statistically significant. The current study also examined the correlation between measures of gratitude and wellbeing and found that the correlations were positive and statistically significant. The findings extend the evidence base concerning the use of gratitude diaries with youth and signify that this intervention may not be effective at increasing well-being in adolescent boys. Possible reasons for not finding a gratitude-based effect and limitations of the study are discussed. Recommendations for future research and implications for practice are noted.
Keywords: Teenage boys; Psychology; Gratitude; Well-being